PEMBELAJARAN IPS PADA KELOMPOK BELAJAR (KEJAR) PAKET B DI PUSAT KEGIATAN BELAJAR MASYARAKAT (PKBM) BARITO KOTA BANJARMASIN - Roghyati Roghyati (Universitas Lambung Mangkurat, 2012)
Nonformal education in Paket A, B, and C is one of the civil right for the citizens to be easily accessible and this is held by PKBM. The research has to objective to know the characteristics of learning community and tutor, the role of PKBM Barito in providing facility and equipment for learning, social learning process of Kejar Paket B celebrated by PKBM Barito. The research uses the qualitative method. The source of data is chosen purposively, and the data collection uses observation, interview, and documentation. The research instruments are interview guide, observation sheet, and documentation. Data analysis by data reduction process, data display, and verification. The research finding say that (1) the characteristics of learning community are in variation whether in age, marital status, profession, education background, motivation, skill, the interestedness to subject, expectation after graduation, and problem in their lives. Whereas characteristics of tutor could be seen from the education level, professional competence, and pedagogic competence; (2) the role of PKBM does not work maximally whether in recruiting community learning, providing facility and equipment for learning celebration, and learning evaluation; however PKBM has the role in recruiting tutor and celebration fund; (3) the learning process of social science for Paket B has fulfilled minimal standar involving preparation, implementation, and evaluation but does not work maximally in learning for the mature learners.Key words: social science learning, Kejar Paket, PKBM role, learning community, tutor.